Root-Cause Analysis for Enhancing Public Health Emergency Preparedness: A Brief Report of a Salmonella Outbreak in the Alamosa, Colorado, Water Supply. Issue 6 (November 2018) - Piltch-Loeb, Rachael; Kraemer, John; Nelson, Christopher; Savoia, Elena; Osborn, David R.; Stoto, Michael A.
Abstract : To demonstrate how public health systems can use root-cause analysis (RCA) to improve learning from critical incidents, the research team utilized a facilitated look-back meeting to examine the public health systems' response to a Salmonella outbreak in the water supply in Alamosa, Colorado. We worked with public health, emergency management agencies, and other stakeholders to identify response challenges related to public health emergency preparedness capabilities, root causes, and lessons learned. The results demonstrate that RCA can help identify systems issues that, if addressed, can improve future responses. Furthermore, RCA can identify more basic issues that go beyond a specific incident or setting, such as the need for effective communication and coordination throughout the public health system, and the social capital needed to support it.